2016
DOI: 10.3389/fpls.2016.01246
|View full text |Cite|
|
Sign up to set email alerts
|

An Ethylene-Protected Achilles’ Heel of Etiolated Seedlings for Arthropod Deterrence

Abstract: A small family of Kunitz protease inhibitors exists in Arabidopsis thaliana, a member of which (encoded by At1g72290) accomplishes highly specific roles during plant development. Arabidopsis Kunitz-protease inhibitor 1 (Kunitz-PI;1), as we dubbed this protein here, is operative as cysteine PI. Activity measurements revealed that despite the presence of the conserved Kunitz-motif the bacterially expressed Kunitz-PI;1 was unable to inhibit serine proteases such as trypsin and chymotrypsin, but very efficiently i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
9
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 72 publications
4
9
0
Order By: Relevance
“… 3,43 By contrast, AtSerpin1 expression was constitutive and insensitive to phytohormones ( refs. 3 & 43 , and unpublished results).…”
Section: Introductionmentioning
confidence: 57%
“… 3,43 By contrast, AtSerpin1 expression was constitutive and insensitive to phytohormones ( refs. 3 & 43 , and unpublished results).…”
Section: Introductionmentioning
confidence: 57%
“…We found that also ethylene can trigger Kunitz-PI;1 expression in the apical hook and augment arthropod deterrence of etiolated seedlings, whereas inhibition of ethylene biosynthesis reduced isopod resistance. 57 Thus complex regulatory circuits operate to protect etiolated seedlings against biotic and abiotic foes in their environment.…”
Section: Discussionmentioning
confidence: 99%
“…This evolutionary trend suggests that type-II WSCPs may have at least one more function in addition to Chl binding. While the specific nature of this function, and its physiological role remain to be determined, the sequence and structural homology between type-II WSCPs and STI [3] and other plant protease inhibitors [38,39], as well as biochemical and physiological evidence [4][5][6][7][8][9][10][11][12], suggest that they may serve as serine-and/or cysteine protease inhibitors to protect against biotic or abiotic stress [5,[7][8][9][10][11][12][13], or to regulate endogenous protease activities [4,14,15].…”
Section: Implications To Wscp Evolution and Physiological Rolesmentioning
confidence: 99%
“…Only a few are water-soluble, including the bacteriochlorophyll-binding Fenna-Matthews-thylakoids and do not participate in photosynthetic reactions. Furthermore, the sequences and structures of type-II WSCPs classify them as part of the Kunitz soybean trypsin inhibitor (STI) superfamily [3], and some were shown to inhibit serine [4] and/or cysteine [5,6] proteases. Their high levels of expression in response to various plant stress conditions such as drought, salinity, and heat [7][8][9][10][11][12], led to suggestions of their possible role in plant defense against herbivores [5,13], or in regulation of endogenous protease activities [4,14,15].…”
Section: Introductionmentioning
confidence: 99%